التطور التاريخي لأجهزة الجمنا ستك الفني للرجال منذ عام 1881م ولغاية عام 2017 م: Historical Development of Men Artistic Gymnastics Code Since 1881 Until 2017 - Majeed, Saleh; Sakran, Jamal (Journal of Physical Education, 2018)
لThe study of the history and development of sports is of great importance because sport is considered the first pillar of culture. Gymnastics is one of the important sports; the gymnasiums on which athletes compete today in the Olympics, World Championships, and continentals there are (6) devices from the first Olympic Games to the last 2016 Olympic Games in Brazil. There have been many changes in the gymnasiums, some of them were radical.The importance of research lies in studying Men's Artistic Gymnastics apparatuses and their development. The researcher traced the history of each apparatuses then the developments of each apparatus. The results of the research showed that the jumping vault is the oldest of the gymnastic apparatus used by the Romans before 400BC for horse riding training and military purposes. The soldiers of Alexander the Great used a large wooden horse for military training and building strength of the body. During the first Olympic Games, gymnastics participated in eight events without floor exercises that was introduced during the thirties of the twentieth century. Finally the researcher concluded that no new apparatus was added in Gymnastic.